Detoxication in Critical Conditions: an Insight into the Scientific Problem in the XXI Century (Review) - S. E. Khoroshilov; A. V. Nikulin (Общая реаниматология, 2018)
Endogenous intoxication as a typical pathological process has always been one of the key issues in all areas of medicine, especially in intensive care. Accumulation of endogenous toxic substances is an integral component of any critical condition. It accompanies severe trauma, generalized infections and destructive diseases of the cavity organs. The loss of the function of detoxification systems in multi-organ failure causes the progression of endotoxicosis and the disruption of oxygen transport (in the organs of detoxification as well), hence closing the vicious cycle of thanatogenesis.Endogenous intoxication is a multidisciplinary problem being a matter of interest in different areas of modern medical science, experimental pathophysiology and biomedical technology. As a result new effective methods of efferent treatments of critical conditions are introduced into clinical practice. For many years theoretical and applied issues aimed at solving the problem of endotoxicosis have been the focus of studies in the V. A. Negovsky Research Institute of General Reanimatology of the Russian Academy of Medical Sciences (now the Federal Research and Clinical Center of Intensive Care Medicine and Rehabilitology). In the presented review we have tried to generalize the main results of the Institute's activities in this direction.